The multi-pass deformation of Ti-6Al-4V - Sikhondze, Bridget Gcinaphi (Centre for Materials Engineering, 2018)
Ti-6Al-4V is a two phase alloy used in the aerospace, military and biomedical industries. The thermomechanical processing (TMP) of Ti-6A-4V involves the breakdown of the ingot microstructure at temperatures above the beta transus (Tβ) into fine lamellar colonies. Subsequent hot deformation is carried out at temperatures within the two phase region to produce a microstructure that is either equiaxed or bimodal. However, to avoid the formation of shear bands, voids or cracks within the final microstructure, this secondary fabrication is carried out at slow speeds, and these render the TMP of titanium a time consuming and expensive process. This project aims to investigate the possibility of using a steckel mill for the TMP of Ti6Al4V. A steckel mill is a single stand reversing mill with 2 coiler furnaces on either side. These furnaces allow for the annealing of strip metal in between passes thus keeping the strip at a high temperature throughout processing. In this way, reversing passes can occur indefinitely until a desired gauge thickness is achieved. A steckel mill therefore represents a cheaper and faster method to produce metal sheet or plate. Ti-6Al-4V cylinders with a diameter of 10mm and length of 15mm were uniaxially compressed in the Gleeble 3800. Hot compression was carried out isothermally in a 3 pass schedule at temperatures of 850°C, 950°C and 1050°C. The strain was kept constant at 0.48 and strain rates of 1/s and 10/s employed. Interpass times corresponding to a strain rate of 10/s were 44s and 77s, whilst those corresponding to a strain rate of 1/s were 324s and 712s. Statistical analysis in the form of analysis of variance (ANOVA) was used to determine the parameter most influential on the microstructural evolution of Ti-6Al-4V and the Taguchi method used to identify the optimum parameters suitable for the TMP of Ti-6Al-4V using a steckel mill. Three successive passes at 850°C, 1/s resulted in a microstructure consisting of coarse, deformed grains and some finer recrystallised grains. The influence of a low strain rate was such that it promoted recrystallisation at this temperature, while that of interpass time brought about recrystallisation and grain growth. At the same temperature and a strain rate of 10/s, less recrystallisation, together with a heavily deformed microstructure was observed. This was due to the heterogeneous distribution of strain which was a consequence of the high strain rate used. At 950°C, at both 1/s and 10/s, 1 pass resulted in a bimodal microstructure. With subsequent passes, the amount of equiaxed alpha was observed to increase. This increase was a result of a strain induced phase transformation (SIT) from beta to alpha at high temperatures. The extent of this transformation increased with an increase in strain rate. Therefore, after 3 consecutive passes at 10/s, a fully alpha (though heavily deformed) microstructure was formed. A subsequent post deformation heat treatment would lead to recrystallisation of these grains and a microstructure consisting of refined equiaxed grains the result. After 1 pass at 1050°C, at either 1/s or 10/s, a Widmanstätten microstructure was formed. However, after 3 consecutive passes at 1/s, the microstructure remained mostly Widmanstätten whilst at 10/s, a bimodal microstructure was formed. The combination of a high strain rate, low interpass times, sequential strain imparted on the sample as well as the high temperature at which the compressions were carried out, elevated the extent to which a strain induced phase transformation from alpha to beta proceeded. Statistical analysis using ANOVA and the Taguchi method revealed that a schedule of 3 passes performed at 1050°C, 1/s and the corresponding interpass times as being the optimum parameters for the TMP of Ti-6Al-4V during steckel mill rolling. Analysis of the microstructural evolution across all 3 temperatures, however, showed that 3 passes carried at 950°C, 10/s, with interpass times of 44s and 77s, as being the optimum parameters. Steckel mill rolling of Ti-6Al-4V has thus been confirmed as a feasible process for the production of Ti-6Al-4V sheet material.